The impact of Industry 4.0 on the relationship between TPM and maintenance performance - Tortorella, Guilherme; Saurin, Tarcisio Abreu; Fogliatto, Flavio Sanson; Tlapa, Diego; Moyano-Fuentes, José; Gaiardelli, Paolo; Seyedghorban, Zahra; Vassolo, Roberto; Mac Cawley, Alejandro Francisco; Sunder, M. Vijaya; Sreedharan, V. Raja; Sena, Santiago Alfredo; et al. (Emerald, 2022)
Purpose In this paper, the authors examine the impact of Industry 4.0 (I4.0) technologies on the relationship between total productive maintenance (TPM) practices and maintenance performance. Design/methodology/approach Data collection was carried out through a multinational survey with 318 respondents from different manufacturing companies located in 15 countries. Multivariate data techniques were applied to analyze the collected data. Diffusion of innovations theory (DIT) was the adopted theoretical lens for our research. Findings The authors’ findings indicate that I4.0 technologies that aim to process information to support decision-making and action-taking directly affect maintenance performance. Technologies oriented to sensing and communicating data among machines, people, and products seem to moderate the relationship between TPM practices and maintenance performance. However, the extent of such moderation varies according to the practices involved, sometimes leading to negative effects. Originality/value With the advances of I4.0, there is an expectation that several maintenance practices and performance may be affected. Our study provides empirical evidence of these relationships, unveiling the role of I4.0 for maintenance performance improvement.
Keywords: Industry 4.0; Total productive maintenance; Performance; Empirical study